2015
DOI: 10.1007/s10545-015-9856-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of megaconial congenital muscular dystrophy due to choline kinase beta gene defects in a series of 15 patients

Abstract: A new form of congenital muscular dystrophy (CMD) with multisystem involvement and characteristic mitochondrial structural changes, due to choline kinase beta (CHKB) gene defects has been characterized by intellectual disability, autistic features, ichthyosis-like skin changes, and dilated cardiomyopathy. We define the clinical characteristics in 15 patients, from 14 unrelated families with so-called 'megaconial CMD', all having mutations in CHKB. Core clinical phenotype included global developmental delay pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 19 publications
(23 reference statements)
0
15
0
Order By: Relevance
“…CI has been reported in various types of CMD. Cardiac involvement, in particular, appears to occur in patients carrying mutations in the LMNA (arrhythmias, dCMP), 72) COL6A (dCMP, systolic dysfunction requiring HTX), 73) 74) POMT1 (aortic root ectasia, systolic dysfunction), 75) CHKB (dCMP, systolic dysfunction, congenital heart defects), 76) and LAMA2 (dCMP) 77) 78) genes. Additionally, CI has been reported in patients with Fukuyama congenital muscular dystrophy (dCMP, systolic dysfunction) due to FKTN mutations, 79) congenital muscular dystrophy with alpha-dystroglycan deficiency (dCMP, CCDs, mitral regurgitation), 80) and in merosin-positive congenital muscular dystrophy (systolic and diastolic dysfunction).…”
Section: Resultsmentioning
confidence: 99%
“…CI has been reported in various types of CMD. Cardiac involvement, in particular, appears to occur in patients carrying mutations in the LMNA (arrhythmias, dCMP), 72) COL6A (dCMP, systolic dysfunction requiring HTX), 73) 74) POMT1 (aortic root ectasia, systolic dysfunction), 75) CHKB (dCMP, systolic dysfunction, congenital heart defects), 76) and LAMA2 (dCMP) 77) 78) genes. Additionally, CI has been reported in patients with Fukuyama congenital muscular dystrophy (dCMP, systolic dysfunction) due to FKTN mutations, 79) congenital muscular dystrophy with alpha-dystroglycan deficiency (dCMP, CCDs, mitral regurgitation), 80) and in merosin-positive congenital muscular dystrophy (systolic and diastolic dysfunction).…”
Section: Resultsmentioning
confidence: 99%
“…In those cases, ichthyosis in proximal areas with fine scaling was suggested as an important clue to the diagnosis. The largest megaconial CMD patient series by Haliloglu et al demonstrated that ichthyosis-like changes was the most frequent (11/15) skin change in megaconial CMD [ 8 ]. Nummular eczema, which is shown in the elder sister of our patients, has not been described before and the symptoms improved after topical corticosteroid therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Differential expression patterns [116,117], mitochondrial activity [118], and neuromuscular junctions [119] are all effects of ChoKβ deficiency in mice. Inactivating mutations in the CHKB gene have been linked to human muscular dystrophy and myopathy in several recent studies [11,[120][121][122][123][124][125][126][127][128]. Since a lack of ChoKβ activity causes muscular dystrophy, any intervention that restores ChoKβ activity can help to restore normal muscle development in this pathological situation.…”
Section: Choks More Than Metabolism Enzymes?mentioning
confidence: 99%